Highly homogeneous antibody modification through optimisation of the synthesis and conjugation of functionalised dibromopyridazinediones. Issue 8 (6th February 2018) - Bahou, Calise; Richards, Daniel A.; Maruani, Antoine; Love, Elizabeth A.; Javaid, Faiza; Caddick, Stephen; Baker, James R.; Chudasama, Vijay
Abstract : Herein we report novel protocols for the generation and application of dibromopyridazinediones, an exciting class of disulfide bridging reagents. Abstract : Due to their exquisite cysteine-selectivity, excellent stability, and ability to functionally rebridge disulfide bonds, dibromopyridazinediones are emerging as an exciting new class of bioconjugation reagents, particularly in the field of antibody conjugation. Despite this, relatively little work has been performed on the optimisation of their synthesis and subsequent reaction with immunoglobulins. Herein we present a novel synthetic route towards functionalised dibromopyridazinediones, proceeding via an isolatable dibromopyridazinedione-NHS ester. Reaction of this activated intermediate with a variety of amines produces functional dibromopyridazinediones in good to excellent yields. The disulfide rebridging capacity of these reagents was optimised on the clinically relevant IgG1 trastuzumab, resulting in a general method which allows for the generation of site-selectively modified native trastuzumab with over 90% homogeneity (no disulfide scrambling) without the need for protein engineering or enzymatic conjugation.